Impact of Shunt FACTS Devices on Security Constrained Unit Commitment - G. A. M. Hosaini Hajivar; S. S. Mortazavi (International Journal of Applied Power Engineering (IJAPE), 2016)
Shunt FACTS Devices (SFD) would play an important role in maintaining security and reduce total generation cost in the economical operation of power systems. The application of this device to the AC model of securityconstrained unit commitment (SCUC) for the day ahead scheduling is presented in this paper. The proposed AC model of SCUC with SFD would include active and reactive power flow constraints which increase the network controllability at normal operation and contingency. A general SFD model is introduced for the reactive power management in SCUC which is based on the reactive power injection model (RPIM). The case studies demonstrate the effectiveness of the SFD application to SCUC with AC network constraints. Meanwhile simulation results demonstrate the combined use of these devices to SCUC have a significant impact on maintaining network security, preventing load shedding, lower total generation cost and increase using the maximum capacity of the existing transmission network.